Startup hell - Rozakis, Caitlin (Rozakis, Caitlin. Everyday enchantments, 2026)
"Morgan Blackwater's mother is a kickass, world-saving, demon-slaying Shadow Council wizard. As for Morgan? Morgan's a junior salesperson at a tech startup that can't even decide what its product is. But with magic dyslexia and a disinclination to kick ass, Morgan is doing her best carving out a niche for herself in the mundane world. Leaving work late one night, she discovers her boss dead from the effort of summoning a demon to trade his soul in order to make his quarterly target. The disturbingly-attractive demon, Lucareoth (Luke for short), is trapped here until he finds someone to sell their soul. While trying to sneak Luke out of the building, Morgan runs into her infamous mother. Apparently, someone has been summoning demons and she's here to get to the bottom of it. Trying to protect Luke from her mother, Morgan gets sucked into the Infernal Plane and discovers hell really is a corporate nightmare. She only gets back home with a promise to deliver a human soul of her own. While her coworkers are really annoying, she's not willing to sacrifice their souls. The company's tech bro CEO, though, is another story"--Publisher's website.